Law enforcement and criminality: Europe vs. USA - Dominique M. Demougin; Robert Schwager (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
We use a stylized model to show that, if transfers to the poor are founded on a security argument, there is a negative trade-o between law enforcement expenditures and criminality. In contrast, if transfers are based on altruism, the correlation between the same variables may appear positive. We argue that it provides a plausible explanation for the startling dierence between the US and Europe in crime statistics and law enforcement expenditures.
Keywords: H3; K0; 330; Criminality; law enforcement; social system; Kriminalpolitik; Kriminalität; Einkommensverteilung; Innere Sicherheit; Altruismus; Theorie; USA; Westeuropa